The Theological Imperative of Marine Ecosystem Conservation via Mangrove Forest Preservation: A Study of the Social Construction of Kyai Nahdlatul Ulama and Muhammadiyah - Fannani, Bakhruddin; Ma’arif, A. Samsul (KARSA Journal of Social and Islamic Culture, 2024)
This article analyzes the theological urgency of preserving marine ecosystems through mangrove forest conservation in a study of the social construction of Nahdlatul Ulama and Muhammadiyah Kyai in Ujungpangkah District, Gresik. Social construction theory plays an important role in shaping society's views on the need to protect the marine environment, which is increasingly threatened by the pace of industrialization. Using the social construction theory framework by Peter L. Berger and Thomas Luckmann, this research analyzes how Nahdlatul Ulama and Muhammadiyah Kyai construct a theology of marine ecosystem conservation and connect it with mangrove forest conservation. Data was collected through interviews and content analysis of lectures and religious literature through a qualitative approach. The research results reveal that Nahdlatul Ulama and Muhammadiyah Kyai have formed a social construction that prioritizes theological values ​​in the context of environmental conservation, especially marine ecosystems through mangrove forest conservation. This construction provides a spiritual and moral foundation for society in the face of ecological change and rapid industrialization. This research provides new insight into the potential role of religion in environmental conservation and provides an in-depth view of the urgency of mangrove forest conservation from the perspective of the social construction of Nahdlatul Ulama and Muhammadiyah Kyai.